Absent-mindedness and injury of the ascending reticular activating system in a patient with mild traumatic brain injury: A case report. Issue 51 (December 2017) - Jang, Sung Ho; Seo, Jeong Pyo
Abstract: Rationale: No study on the association of absent-mindedness and injury of the ascending reticular activating system (ARAS) has been reported. We report on a patient who showed absent-mindedness and injury of the ARAS following mild traumatic brain injury. Patient concerns: The patient complained of absent-mindedness since the head trauma, which was mainly observed while dining for several (5–10) minutes approximately 3 to 4 times a day: according to the patient's family, he usually stopped eating while holding the spoon in the air for approximately 5∼10 minutes. Diagnoses: A 19-year-old man suffered from head trauma resulting from being hit on his head by a falling glass from a large window (1.5 × 2 m, approximately 100 kg) at a cafe. Interventions: His absent-mindedness showed slow improvement with the passage of time and had almost disappeared at seven months after onset. Outcomes: The lower portion of both lower dorsal ARAS and the upper portion of the left lower ventral ARAS of the patient were thinner, and partial tearing was observed in the right lower ventral ARAS. Decreased neural connectivity of the intralaminar thalamic nucleus to the prefrontal cortex, basal forebrain, parietal cortex, and occipital cortex was detected in both hemispheres. Lessons: Injury of the ARAS and injury of the cerebral cortex was demonstrated in a patient with absent-mindedness following mild traumatic brain injury. The absent-mindedness in this patient might be related to the injury of the ARAS.